1993
DOI: 10.1148/radiology.189.2.7692465
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter chemoembolization of progressive carcinoid liver metastasis.

Abstract: Chemoembolization is safe and effective for palliation of carcinoid liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
4

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(67 citation statements)
references
References 0 publications
1
60
1
4
Order By: Relevance
“…With a tumour response rate of 37% (CI 95%: 28 -49%), our results are in the range of previous studies regarding treatment's efficacy (Ruszniewski et al, 1993;Therasse et al, 1993;Diaco et al, 1995;Dominguez et al, 2000;Gupta et al, 2003;Kress et al, 2003;O'Toole et al, 2003;Roche et al, 2003). Recently, Roche et al (2004) reported a response rate of 74%, much higher than what we observed.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…With a tumour response rate of 37% (CI 95%: 28 -49%), our results are in the range of previous studies regarding treatment's efficacy (Ruszniewski et al, 1993;Therasse et al, 1993;Diaco et al, 1995;Dominguez et al, 2000;Gupta et al, 2003;Kress et al, 2003;O'Toole et al, 2003;Roche et al, 2003). Recently, Roche et al (2004) reported a response rate of 74%, much higher than what we observed.…”
Section: Discussionsupporting
confidence: 82%
“…Post embolisation syndrome was reported only after 47% of procedures in our series, whereas its frequency is usually reported to be higher (Ruszniewski et al, 1993;Therasse et al, 1993;Diaco et al, 1995;Dominguez et al, 2000;Gupta et al, 2003;Kress et al, 2003;O'Toole et al, 2003;Roche et al, 2003Roche et al, , 2004. We can account for this discrepancy by assuming that as this side effect is extremely frequent it was probably not systematically reported, so that we recorded it only when considered significant, that is, responsible for an extension of hospital stay or the use of major analgesics.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, the hepatic metastases are angiographically hypervascular, extrahepatic metastases are unusual, and systemic chemotherapy is often ineffective. All of these characteristics have led investigators to attempt both palliative and definitive treatment with chemoembolization [42,80,[85][86][87][88][89][90][91][92][93][94][95].…”
Section: Neuroendocrine Metastasesmentioning
confidence: 99%
“…Carcinoid tumors, although rare, are the most frequent of all endocrine tumors of the gut [1]. The release of a great variety of biologically active hormones and amines directly into the systemic circulation by hepatic metastases causes symptoms of the carcinoid syndrome and severely compromises the patient's lifestyle [2,3].…”
Section: Departmentmentioning
confidence: 99%